1996
DOI: 10.1111/j.1574-695x.1996.tb00222.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of cell-associatedN-acetyl-d-glucosamine specific haemagglutinin in the adhesion ofVibrio choleraeO1 to rabbit intestinal epithelial cells in vitro

Abstract: Previously a N-acetyl-D-glucosamine specific cell-associated haemagglutinin (HA) had been purified from a Vibrio cholerae O1 strain. This study documents the role of this purified HA as an adhesin of V. cholerae O1. A significant inhibition in the adhesion of V. cholerae O1 bacterial cells to isolated rabbit intestinal brush borders (RIBB) was observed when the latter were pretreated with purified HA in ELISA. Antibody raised against purified HA and Fab (IgG) fragment of this serum inhibited adhesion of the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Bacterial ligands mediating adhesion to chitin by a specific binding to Nacetylglucosamine (GlcNAc) have been shown to be present in V. cholerae classical strains. A cellassociated GlcNAc specific hemagglutinin (HA) was purified from V. cholerae by affinity chromatography on a chitin column, followed by BioGel filtration (16). Chitin-binding proteins (CBPs) associated with the cell wall have been described by Tarsi and Pruzzo (17) and Zampini et al (18), who extended previous studies on Vibrio harveyi (19) and Vibrio alginolyticus (20), and identified two surface proteins (36 kDa and 53 kDa) involved in adhesion of V. cholerae classical strains to chitin beads and copepods.…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial ligands mediating adhesion to chitin by a specific binding to Nacetylglucosamine (GlcNAc) have been shown to be present in V. cholerae classical strains. A cellassociated GlcNAc specific hemagglutinin (HA) was purified from V. cholerae by affinity chromatography on a chitin column, followed by BioGel filtration (16). Chitin-binding proteins (CBPs) associated with the cell wall have been described by Tarsi and Pruzzo (17) and Zampini et al (18), who extended previous studies on Vibrio harveyi (19) and Vibrio alginolyticus (20), and identified two surface proteins (36 kDa and 53 kDa) involved in adhesion of V. cholerae classical strains to chitin beads and copepods.…”
Section: Introductionmentioning
confidence: 99%